Nutritional requirements and fermentation condition for acetic acid production from agricultural fruit waste - Selvanathan, Yashini K; Saleha, Shamsudin; Norazwina, Zainol; Nasratun, Masngut (Wiley, 2024)
Studies on agricultural fruit waste fermentation for acetic acid production have focused on understanding its nutrient requirements. The present systematic literature review aimed to assess the potential and additional nutrients necessary for optimised acetic acid production from fruit waste. Fermentation conditions and techniques employed for the alcoholic and acetous fermentation stages were also evaluated to establish their significant effects on acetic acid yield.